Card Sort Dalam Menulis Karangan Sederhana Bahasa Jerman - Yolanda Farhana; Muh Anwar; Wahyu Kurniati Asri (Phonologie : Journal of Language and Literature, 2022)
Abstract. This research is a quasi-experimental research that aims to find out the application of card sort in writing simple essays for students of class XI IPS SMA Negeri 3 Makassar. The independent variable in this study was the use of card sort, while the dependent variable was the simple essay writing skills of the XI IPS class students of SMA Negeri 3 Makassar. The population in this study were all students of class XI IPS SMA Negeri 3 Makassar as many as 3 classes, while the sample was class XI IPS 2 as an experimental class with 33 students and class XI IPS 1 as a control class with 33 students. The research data were obtained by giving a simple essay writing test for Essen und Trinken in the form of a pretest and posttest. Based on the results of inferential statistical analysis using the t-test, it was obtained that tcount 3,264> ttable 1,669 at an alpha level of 0.05. While the average value before using card sort is 73.31 and the average value after using card sort is 78.46. Thus, there is a difference in the average value before and after the learning media in the form of card sort is given.Keyword: Learning Media, Card Sort, Simple Essay